Contemporary da’wah challenges: The normalization of infidelity in WeTV series and its impact on urban Muslim couples - Robby Aditya Putra; Dede Mercy Rolando; Maulida Fitri; Muhamad Munir (Islamic Communication Journal, 2026)
This study aims to examine the challenges of contemporary Islamic da'wah in addressing the normalization of infidelity in WeTV digital film series and its implications for urban Muslim couples in Bandar Lampung. This study employed a qualitative research design based on audience reception analysis, using in-depth interviews with six urban Muslim couples. Data were interpreted through the lenses of Social Learning Theory, Cultivation Theory, and the Cognitive–Affective–Behavioral approach. The findings reveal that WeTV series centered on infidelity do not directly encourage urban Muslim couples to imitate infidelity-related behavior. However, repeated exposure to such narratives influences how audiences understand marital conflict, emotional neglect, and modern relationships. Media influence appears more prominently in emotional engagement and interpretive shifts rather than in actual behavioral change. Although participants continued to uphold Islamic values concerning fidelity and marital ethics, digital media created a symbolic space of negotiation in which audiences normatively rejected infidelity while simultaneously expressing empathy toward the emotional conditions experienced by film characters. This study implies that contemporary Islamic da’wah is no longer concerned solely with the transmission of normative religious teachings, but also with the need to develop critical media literacy and strengthen Muslim family resilience amid the continuing expansion of digital culture. ***** Penelitian ini bertujuan untuk mengkaji tantangan dakwah Islam kontemporer tentang normalisasi perselingkuhan dalam serial film digital WeTV serta dampaknya terhadap pasangan Muslim urban di Bandar Lampung. Penelitian ini menggunakan desain penelitian kualitatif yang didasarkan pada analisis resepsi audiens (audience reception analysis), dengan pengumpulan data melalui wawancara mendalam terhadap enam pasangan Muslim perkotaan. Data diinterpretasikan menggunakan kerangka teoretis Social Learning Theory, Cultivation Theory, dan pendekatan Cognitive–Affective–Behavioral.  Penelitian ini menemukan bahwa serial WeTV bertema perselingkuhan tidak secara langsung mendorong pasangan Muslim urban untuk meniru perilaku perselingkuhan. Namun, paparan narasi yang berulang memengaruhi cara audiens memahami konflik rumah tangga, pengabaian emosional, dan relasi modern. Temuan penelitian menunjukkan bahwa pengaruh media lebih terlihat pada keterlibatan emosional dan perubahan interpretasi dibandingkan perubahan perilaku secara nyata. Meskipun partisipan tetap mempertahankan nilai-nilai Islam mengenai kesetiaan dan etika pernikahan, media digital menghadirkan ruang negosiasi simbolik di mana audiens secara normatif menolak perselingkuhan tetapi pada saat yang sama menunjukkan empati terhadap kondisi emosional karakter dalam film. Penelitian ini berimplikasi pada dakwah yang tidak hanya dihadapkan pada persoalan penyampaian ajaran normatif, tetapi juga pada kebutuhan untuk membangun literasi media kritis dan penguatan ketahanan keluarga Muslim di tengah perkembangan budaya digital.